2023
DOI: 10.1002/pd.6390
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of the first‐trimester nuchal translucency between the 95th–99th percentiles

Ilaria Fantasia,
Silvia Catagini,
Giulia Zamagni
et al.

Abstract: Objectives To evaluate the clinical significance of nuchal translucency (NT) between the 95th–99th percentile in terms of typical and atypical chromosomal abnormalities (ACAs), associated fetal congenital defects and postnatal outcome. Methods A retrospective cohort study of fetuses with NT between the 95th–99th percentile. Data regarding the rate of associated fetal defects, genetic abnormalities and postnatal outcome were collected. Results A total of 306 cases of fetuses with an NT between the 95th–99th per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Firstly, it relied on retrospective data collection. Secondly, the incidence of structural defects in fetuses with NT measurements between 2.5–2.9 mm was higher than previously reported in the literature ( 7 , 17 ). This discrepancy may be attributed to the fact that some pregnant women opted for NIPT instead of invasive prenatal diagnosis, potentially influencing the observed incidence of structural defects.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Firstly, it relied on retrospective data collection. Secondly, the incidence of structural defects in fetuses with NT measurements between 2.5–2.9 mm was higher than previously reported in the literature ( 7 , 17 ). This discrepancy may be attributed to the fact that some pregnant women opted for NIPT instead of invasive prenatal diagnosis, potentially influencing the observed incidence of structural defects.…”
Section: Discussioncontrasting
confidence: 62%
“…Further underscoring this importance, our study found fetal congenital defects in 18.4% of fetuses with NT 2.5–2.9 mm. Fantasia et al ( 17 ) also recognized the significance of mild NT elevations (between the 95th and 99th percentiles), reporting rates of 12.1% for chromosomal abnormalities and 13.7% for congenital defects. However, it’s important to note that an NT of 3.0 mm does not directly correlate to the 95th percentile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite showing a good performance of such a scan in their center, Pruthi and colleagues in Canada do not recommend implementing detailed first trimester anatomy scanning outside tertiary referral centers 10 . Research continues to bring new insights on the diagnostic ability of the early ultrasound scan: the fetal heart, 11 the central nervous system 12,13 skeletal dysplasias 14 and increased nuchal translucency 15 . Also, among the first trimester screening strategies for congenital anomalies discussed by Bardi et al., early anatomical assessment occupies a central role, from the most advanced to more traditional screening menus 7…”
Section: Figurementioning
confidence: 99%
“…10 Research continues to bring new insights on the diagnostic ability of the early ultrasound scan: the fetal heart, 11 the central nervous system 12,13 skeletal dysplasias 14 and increased nuchal translucency. 15 Also, among the first trimester screening strategies for congenital anomalies discussed by Bardi et al, early anatomical assessment occupies a central role, from the most advanced to more traditional screening menus. 7 One of the concerns with early fetal anatomy ultrasound, which can facilitate earlier terminations for fetal anomalies, is the potential loss of information from a detailed autopsy.…”
mentioning
confidence: 99%